Isolation, Identification and Optimization of Potential Keratinase Enzyme-Producing Bacteria from Poultry Soil: Synthesis of Zinc Oxide Keratinase-based Nanoparticles and Their Application in Plant Growth Promotion - M. Jisha; Anitha Subash; Vidya Valsaraja; A. Shobana (HAYATI Journal of Biosciences, 2026)
Poultry farming produces large amounts of feather waste, which is hard to manage due to its tough keratin content and limited eco-friendly disposal methods. Keratin-degrading microorganisms offer a cost-effective and viable alternative for the management of feather waste compared to chemical treatment methods. The present study aimed to focus on the identification and optimisation of potential keratinolytic enzyme-producing bacteria from the poultry soil. Through a molecular identification method (16S rRNA), the potent bacterium was identified as belonging to the species Mesobacillus thioparans. The one variable at a time approach (OVAT) investigation revealed that a high level of keratinase activity was detected at pH 7.0, 40°C, with glucose as a better carbon source and yeast  as the preferred nitrogen source. Along with optimisation, we also demonstrated the beneficial use of the partially purified keratinase enzymes via synthesising zinc oxide-based nanoparticles (ZnO NPs) and evaluating their potential as plant growth promoters. According to this study, keratinase-ZnO NPs considerably improved the physiological and biochemical properties of the plants compared to the control group. There were no significant variations of chlorophyll producing plants' however, significant variations were observed in the protein and carbohydrate concentrations in enzyme treated plants, recording protein content of 3.02±0.43 µg/g and carbohydrate of -9.8±1.01 µg/g), compared to the control plants (protein is 1.24±0.16 µg/g and carbohydrate -5.3±0.76 µg/g). This study sheds new light on the application of microbially derived keratinase enzyme-based NPs for plant growth promotion potential.